Discipler's guide - Hanks, Billie; (1944-...) (China, 2009)
Great book by Billie Hanks Jr. Several of my Chaplain friends have used, `A Call to Joy` to have new Christian inmates understand and grow in their new spiritual life and walk in Jesus Christ. This book is well organized and gives a good bible foundation for a believer's faith and testimony.
Keywords: Discipleship (Religion)